Sex difference in the association between creatinine-to-cystatin C ratio and metabolic syndrome among Chinese adults - Chen, Jo-Hsuan; Chen, Jau-Yuan; Chen, Yi-Chuan; Li, Wen-Cheng (Frontiers in Endocrinology, 2024)
Background Metabolic syndrome (MetS), characterized by central obesity, insulin resistance, dyslipidemia, and hypertension, affects 20-25% of the global population. The creatinine-to-cystatin C ratio (CCR) is an indicator of skeletal muscle mass. While CCR may play a role in MetS development, sex differences in these associations are not fully understood. Therefore, this study aimed to investigate how CCR levels are associated with MetS in a Chinese adult population, focusing on possible sex disparities. Method We conducted a retrospective cross-sectional analysis of 9,376 adults from Xiamen Chang Gung Hospital between 2014 to 2016. We examined the relationship between CCR and MetS, adjusting for cardiometabolic risk factors. Results The prevalence of MetS was 24.7% in males and 18.0% in females. Interestingly, we observed significant sex differences in the association between CCR quartiles and MetS. Females in the lowest CCR quartile had a significantly higher risk of MetS (odds ratio=1.84). Receiver operating characteristic curve analysis revealed acceptable diagnostic power of CCR for MetS in females (area under the curve=0.65) but not in males. Conclusion Our findings suggest that CCR is an independent risk factor for MetS in females, highlighting the importance of sex-specific assessments when evaluating MetS risk.